Strategic orientation and effects of e-administration: Findings from the miles and snow framework - Liliana Hawrysz (Administrative Sciences, 2020)
Much has been written about the strategic orientation of public administration organizations (prospecting, defending, reacting, and analyzing) and their consequences for organizational effects, but little is dedicated to e-administration. Is the provision of services using IT affecting the adoption of strategic orientation and its effects? The paper is dealing with e-administration issues, specifically in terms of the impact of the Miles and Snow strategic orientation on e-administration effects. To measure e-administration effects, the author's personal tool using the Common Assessment Framework (CAF) criterion has been proposed. The data collection was conducted using the Computer-Assisted Web Interview (CAWI) method, in the period from November 2017 to January 2018. Two hundred and twenty-six Polish organizations took part in the study. The objective of this study, i.e., assessing the impact of strategic orientation and e-administration effects, was achieved by using the Ordinary Least Squares (OLS) method. It is indicated that the Defender orientation is positively associated with the effects of e-administration.
Keywords: 350; e-administration; effects; Miles and Snow framework; strategic orientation